Mechanisms of transcriptional dysregulation in repeat expansion disorders. - Groh, M; Silva, L; Gromak, N (2014)
Approximately 40 human diseases are associated with expansion of repeat sequences. These expansions can reside within coding or non-coding parts of the genes, affecting the host gene function. The presence of such expansions results in the production of toxic RNA and/or protein or causes transcriptional repression and silencing of the host gene. Although the molecular mechanisms of expansion diseases are not well understood, mounting evidence suggests that transcription through expanded repeats plays an essential role in disease pathology. The presence of an expansion can affect RNA polymerase transcription, leading to dysregulation of transcription-associated processes, such as RNA splicing, formation of RNA/DNA hybrids (R-loops), production of antisense, short non-coding and bidirectional RNA transcripts. In the present review, we summarize current advances in this field and discuss possible roles of transcriptional defects in disease pathology.